An integrative literature review of psychosocial factors in the transition to parenthood following non-donor-assisted reproduction compared with spontaneously conceiving couples. (8th August 2021) - Allan, Helen T.; van den Akker, O.; Culley, Lorraine; Mounce, Ginny; Odelius, Anki; Symon, Andrew
Abstract: The paper reports an integrative literature review of research into the psychosocial factors which shape the transition to parenthood in couples following non-donor in vitro fertilization in comparison with those conceiving spontaneously. Nineteen papers of non-donor IVF and SC mothers and fathers were included. Differences between groups were reported for a range of psychosocial measures during the transition from pregnancy to parenthood including: the control couples feel they have over their lives (locus of control), parental adjustment and child behaviour, parental stress, parental investment in the child, self-esteem and self-efficacy, greater levels of protectiveness (separation anxiety) towards child, marital and family functioning, family alliance, marital satisfaction and communication, as well as anxiety, indirect aggression and lowered respect for the child. We have conceptualised these differences as three substantive themes which reflect psychosocial factors shaping transition to parenthood in parents after non-donor AR: namely social support, relationships and emotional well-being, which are in turn influenced by gender differences. These findings have implications for health care professionals' assessment of individual couples' support needs.